Microstructure of fine-grained sediments from mud to shale - Bennett R H; Bryant W R; Hulbert M H (New York Springer-Verlag, 1991)
This compilation of fifty-nine peer-reviewed papers examines clay microstructure in detail with comprehensive sections focusing on microstructure signatures, environmental processes, modeling, measurement techniques, and future research recommendations.
Keywords: Clay-analysis; Sedimentary rocks-analysis; Sediments(Geology)